Strategi Etnografi dalam Implementasi KMA 183 Tahun 2019 pada Pembelajaran Pendidikan Agama Islam di Madrasah - Sutarno, Sutarno; Fiqih, Uky Fatanun (LP2M IAIN kUDUS, 2021)
National education has a function of developing cognitive, affective and psychomotor aspects, as well as the formation of noble personality as a dignified nation's identity. Global changes that are very quick to demand the world of education to respond and adjust to compiling a curriculum that is able to adopt these changes, one that must adjust to the madrasa curriculum. In the KMA regulates graduation standards, core competencies (KI), and basic competencies (KD) for the field of Hadith Qur'an Studies, Akidah Akhlak, Fiqh, SKI, and Arabic which are the peculiarities of madrasas. The purpose of this study was to analyze the application of the application of ethnographic methods in the implementation of KMA 183 of 2019. One aspect that can be measured using an ethnographic approach is an aspect of attitude. To get valid data quality, ethnographic studies have stages 1) selecting community groups (class), 2) investigating to obtain information, 3) processing and interpreting data, and 4) Finalization of data and compiling reports. This research has implications for the application of ethnography in the implementation of KMA 183 of 2019 in PAI learning in madrasah. It is expected that more madrassas are expected to use ethnography to do the size of the quality of attitude.